Microsoft Visual C#: An Introduction to Object-Oriented Programming, 7th Edition - Joyce Farrell (Cengage Learning, 2017)
Guide beginning programmers through the fundamentals of the C# language using its most recent features with Farrell's MICROSOFT® VISUAL C# 2017: AN INTRODUCTION TO OBJECT-ORIENTED PROGRAMMING, 7E. Approachable examples and a clear presentation help students build a strong background in both structured and object-oriented programming concepts. Students master critical fundamental skills that easily transfer to other programming languages. This edition incorporates the most recent versions of both C# and Visual Studio to ensure students have the latest skills necessary for professional success. Hands-on features, video lessons, new debugging exercises, programming exercises, and running case studies keep students actively engaged. A full selection of instructor support provides the tools to reinforce the solid programming skills your students need.